Microwave Preparation, Spectral Studies and Antimicrobial Activities Evaluation of Mn(II),Ni(II), Hg(II),Co(II) and Cu(II) Complexes with Schiff Base Ligand - Al-Shemary, Rehab Kadem Rahem (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
New Schiff base and their Mn(II),Co(II),Ni(II), Cu(II) and Hg(II) complexes formed by the condensation of O-phathaldehyde and ethylene diamine (2:1) to give ligand (L1) in the first step ,then the ligand (L1) with 2- aminophenol (1:2) to give ligand (L2) were prepared by classic addition through microwave method . These compounds (Ligands and complexes) have been diagnosed electronic spectra, FT-IR, 1H-&13C-NMR (only ligand), magnetic susceptibility, elemental microanalysis and molar conductance measurements. Analytical values displayed that all the complexes appeared (metal: ligand) (1:1) ratio with the six chelation. All the compounds appear a high activity versus four types of bacteria such as; (Escherichia coli), (Staphylococcus aureus),(Bacillus btilis), (Staphylococcus aureus) and (Pseudomonas aeruginosin).